The Relationship between Self-Acceptance and Social Support with Self-Confidence in Madrasah Tsanawiyah (Edukasi, 2022)
According to preliminary studies conducted by researchers at the Madrasah Tsanawiyah or equivalent to the junior high school level, there is a phenomenon where some students still feel embarrassed when asking teachers. The results of the preliminary studies also resulted in a moderate level of student confidence. The purpose of this study was to determine the relationship between self-acceptance and social support with the self-confidence of MTs students in Gunungpati District. The method used in the study is the correlational quantitative method, while the sampling used in the study is the proportionate stratified random sampling technique with cluster sampling. The subject of the study was class VII students in 4 MTs. The research location is in Gunungpati District, Semarang. The total population was 463 students with a research sample of 198 students. The measuring instruments used are the confidence scale, the self-acceptance scale, and the social support scale. The results of the study showed that there was a non-negative and significant relationship between self-acceptance and social support with the self-confidence of MTs students in Gunungpati District. That is, the higher the level of self-acceptance and the level of social support, the higher the level of self-confidence. Both independent variables contributed to confidence by 39.1%. Furthermore, researchers are expected to be able to examine self-confidence variables with other variables such as the influence of parenting, peers, motivation, and others.